No difference in high-magnification morphology and hyaluronic acid binding in the selection of euploid spermatozoa with intact DNA - Mongkolchaipak, Suchada (Nature Publishing Group, 2013)
In this study, we compared conventional sperm selection with high-magnification morphology based on the motile sperm organellar morphology examination (MSOME) criteria, and hyaluronic acid (HA) binding for sperm chromosome aneuploidy and DNA fragmentation rates. Semen from 50 severe male factor cases was processed through density gradient centrifugation, and subjected to sperm selection by using the conventional method (control), high magnification at ×6650 or HA binding. Aneuploidy was detected by fluorescence in situ hybridization with probes for chromosomes 13, 18, 21, X and Y, and DNA fragmentation by the terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) method. Spermatozoa selected under high-magnification had a lower DNA fragmentation rate (2.6% vs. 1.7% P=0.032), with no significant difference in aneuploidy rate (0.8% vs 0.7% P=0.583), than those selected by the HA binding method. Spermatozoa selected by both methods had much lower aneuploidy and DNA fragmentation rate than the controls (7% aneuploidy and 26.8% DNA fragmentation rates, respectively). In the high-magnification group, the aneuploidy rate was lower when the best spermatozoa were selected than when only the second-best spermatozoa were available for selection, but the DNA fragmentation rate was not different. In conclusion, sperm selection under high magnification was more effective than under HA binding in selecting spermatozoa with low DNA fragmentation rate, but the small difference (0.9%) might not be clinically meaningful. Both methods were better than the conventional method of sperm selection.